Արաբական երկրների նկատմամբ Թուրքիայի տարածքային հավակնությունները նորագույն շրջանում - Հովհաննիսյան, Նիկոլայ («Զանգակ - 97»)
The Arab-Turkish relations arc one of the eompliealed fields of the Middle Mastern geopolilical realitics of the newst period. It has its reasons-historical, political, inucluding geopolitieal, economic, religious, etc.
Keywords: Պատմություն; Քաղաքականություն